Implementasi Sistem Merit dalam Manajemen Pegawai Negeri Sipil di Kementerian Keuangan Republik Indonesia - Halifa Nurnadhifa; Lilie Syahrina (Widya Manajemen, 2021)
This research is motivated by the importance of managing HR management by using a merit system as a solution to improve the performance of Civil Servants (PNS). In the merit system-based HR management, potential, and competence, both managerial, technical, and socio-cultural are the main pillars. This study aims to determine the application of the merit system in the management of civil servants at the Ministry of Finance of the Republic of Indonesia. The level of application of the merit system at the Ministry of Finance in 2018 and 2019 was in category IV "Sangat Baik". Using a qualitative approach, this descriptive research collects qualitative data through a study of various books, literature, notes, and reports relevant to the implementation of the merit system at the Ministry of Finance of the Republic of Indonesia. The results of the study found that the implementation of the merit system in the management of civil servants at the Ministry of Finance was good and had been carried out in earnest with the commitment of the leadership of the Ministry of Finance.